2002
DOI: 10.3758/bf03194733
|View full text |Cite
|
Sign up to set email alerts
|

The impact of spatiotemporal sampling on time-to-contact judgments

Abstract: When motion in the frontoparallel plane is temporally sampled, it is often perceivedto be slower than its continuous counterpart. This finding stands in contrast to humans' ability to extrapolate and anticipate constant-velocitymotion. We investigated whether this sampling bias generalizesto motion in the sagittal plane (i.e., objects approaching the observer).We employed a paradigm in which observers judged the arrival time of an oncoming object. We found detrimental effects of time sampling on both perceived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 65 publications
1
9
1
Order By: Relevance
“…4a, the observers significantly overestimated TTC, except at the longest designated TTC. This result is compatible with previous studies where overestimation was observed at TTCs smaller than approximately 1,500 ms (Hecht, Kaiser, Savelsbergh, & van der Kamp, 2002;Heuer, 1993;Oberfeld & Hecht, 2008), while underestimation was found at longer TTCs (McLeod & Ross, 1983;Schiff & Detwiler, 1979). In the present experiment, the TTC overestimation decreased as the designated TTC increased from 1,000 to 2,000 ms, as confirmed by a significant effect of TTC.…”
Section: Resultssupporting
confidence: 82%
“…4a, the observers significantly overestimated TTC, except at the longest designated TTC. This result is compatible with previous studies where overestimation was observed at TTCs smaller than approximately 1,500 ms (Hecht, Kaiser, Savelsbergh, & van der Kamp, 2002;Heuer, 1993;Oberfeld & Hecht, 2008), while underestimation was found at longer TTCs (McLeod & Ross, 1983;Schiff & Detwiler, 1979). In the present experiment, the TTC overestimation decreased as the designated TTC increased from 1,000 to 2,000 ms, as confirmed by a significant effect of TTC.…”
Section: Resultssupporting
confidence: 82%
“…Although most experiments using a PM task have found an underestimation of TTC (e.g., McLeod & Ross, 1983;Schiff & Detwiler, 1979), cases of TTC overestimation have also been reported, particularly for extrapolation intervals smaller than 1,000 ms (e.g., Hecht, Kaiser, Savelsbergh, & Van der Kamp, 2002;Heuer, 1993;Smith et al, 2001). The extrapolation intervals in the present experiment were about 1,000 ms.…”
Section: Discussionmentioning
confidence: 99%
“…One type of coincidence-anticipation tasks is prediction-motion tasks, in which the moving object is occluded from view before it reaches the observer or specified point. The subject then indicates a response at the moment of the object's speculated arrival time [Tresilian 1995;Benguigui et al 2003;Hecht et al 2002]. Another subset of coincidence-anticipation tasks is experiments involving interceptive action tasks, such as catching or hitting balls [Caljouw et al 2004;Senot et al 2003;Servos and Goodale 1998;Tresilian 1993].…”
Section: Ii1 Types Of Time-to-contact Experimentsmentioning
confidence: 99%